COMPARATIVE USEFULNESS OF FINANCIAL AND NON-FINANCIAL INDICATORS IN ASSESSING COMPANY VALUE - Jahan Gylyjova (Scholars Digest Publishing, 2025)
This article examines the relative usefulness of traditional financial metrics and non-financial indicators (including ESG indicators, intellectual capital, customer satisfaction, etc.) in assessing company valuation. Based on a review of empirical studies and theoretical approaches, it analyzes the conditions under which non-financial information provides additional information to financial statements, how the market reacts to such information, and the methodological challenges associated with its use in valuation.
Keywords: Higher education, teaching translation, innovation, translation skills, creative education, Iraqi students.